TEACHING MEDIA AND VOCABULARY MASTERY TOWARDS STUDENTS’ SPEAKING SKILL - Nur Faizah; Imam Suseno (INFERENCE: Journal of English Language Teaching, 2019)
The purpose of this research is to find the effect of teaching media and vocabulary mastery towards students’ speaking skill at Private Senior High Schools in Central Jakarta. The research methodology is experiment. The sample is 60 students which consist of 30 for experiment and 30 for control class. The sampling technique used is random sampling. Data collection is testing vocabulary mastery and speaking skill. Data analysis uses descriptive statistic, normality test, homogeneity test, and two ways ANOVA to test hypothesis testing. The research results conclude 1) There is a significant effect of teaching media towards students’ speaking skill. This is proved by the result of (Sig.) is 0,000 < 0,05 and Fo = 381,979. 2) There is a significant effect of vocabulary mastery towards students’ speaking skill. This is proved by the result of (Sig.) is 0,000 < 0,05 and Fo = 136,242. 3) There are no significant interactive effects of teaching media and vocabulary mastery towards students’ speaking skill. This is proved by the result of (Sig.) is 0,109 > 0,05 and Fo = 2,653.